Prevalence of violence to others among individuals with schizophrenia in China: A systematic review and meta-analysis - Guo, Yi; Yang, Xianmei; Wang, Dan; Fan, Ruoxin; Liang, Yiying; Wang, Rongke; Xiang, Hu; Liu, Yuanyuan; Liu, Xiang (Frontiers in Psychiatry, 2022)
Background: Violence to others (hereinafter referred to as “violence-TO”) is common in individuals with schizophrenia. The reported prevalence of violence-TO among schizophrenics ranges widely in existing studies. Improved prevalence estimates and identification of moderators are needed to guide future management and research. Methods: We searched EBSCO, EMBASE, Medline, PubMed, Science Direct, Web of Science, CNKI, VIP, WANFANG data and CBM for relevant articles published before June 5, 2022. Meanwhile, violence-TO was summarized into four categories: a). violence-TO on the reviews of official criminal or psychiatric records (type Ⅰ); b). less serious forms of violence-TO (type Ⅱ); c). physical acts causing demonstrable harm to victims (type Ⅲ); d). homicide (type Ⅳ). We did meta-analysis for the above types of violence-TO respectively and applied subgroup analyses and meta-regression analyses to investigate the source of heterogeneity. Results: 56 studies were eligible in this study and 34 of them were high-quality. The prevalence of type Ⅰ to type Ⅳ in individuals with schizophrenia in China was 23.83% (95%CI: 18.38%-29.75%), 23.16% (95%CI: 8.04%-42.97%), 17.19% (95%CI: 8.52%-28.04%), and 0.62% (95%CI: 0.08%-1.54%) respectively. The results of the subgroup analysis showed that the prevalence of type Ⅰ was higher among subjects in the inland than in the coastal non-economic zone, while the prevalence of type Ⅲ was the highest in the coastal economic zone, followed by the inland region and the lowest in the coastal non-economic zone. The results of multivariate meta-regression analyses showed that: patient source in type Ⅰ (β=0.15, P<0.01), patient source (β=0.47, P<0.01) and proportion of male (β=0.19, P<0.01) in type Ⅱ, age (β=0.25, P<0.01) and GDP per capita (β=0.05, P=0.01) in type Ⅲ were statistically significant. Conclusions: The prevalence of different types of violence-TO and their influencing factors varied. Therefore, the authorities should take different management measures. In addition to individual factors, regional factors may also affect violence-TO, which suggests the need for a multi-sectoral approach to prevention and treatment for subjects in different regions and adopting targeted control strategies. Systematic Review Registration: This study is registered in PROSPERO with number CRD42021269767.